The Effect of the Australian National Firearms Agreement on Suicide and Homicide Mortality, 1978–2015 - Gilmour, Stuart (Am J Public Health, 2018)
Objectives. To investigate the impact of the Australian National Firearms Agreement (NFA) on suicide and assault mortality. Methods. We conducted a retrospective cross-sectional difference-in-difference study of the impact of the NFA on national mortality rates in the Australian population from 1961 to 2015. Results. The NFA had no additional statistically observable impact on firearm-related suicides in women (P = .09) and was associated with a statistically significant increase in the trend in men (P < .001). Trends in non–firearm-related suicide deaths declined by 4.4% per year (95% confidence interval [CI] = 4.1%, 4.8%) in men after the introduction of the NFA and increased in women by 0.3% (95% CI = 0.1%, 0.7%). Trends in non–firearm-related homicides declined by 2.2% per year (95% CI = 1.5, 3.8%) in women and 2.9% per year (95% CI = 2.0%, 3.7%) in men after the introduction of the NFA, with a statistically significant improvement in trends for women (P = .04) but not for men (P = .80). Conclusions. The NFA had no statistically observable additional impact on suicide or assault mortality attributable to firearms in Australia.